Molecular response of Physarum melleum GZ381 to anatase TiO2 nanoparticles: Characteristic and application - Zhi Zhang; Cheng Xin Wu; Qin Hui Lu; Xiu Yi Liang; Zhi Cheng Liang; Yi Yang (Emerging Contaminants, 2025)
Environmental pollution caused by nano titanium dioxide (nTiO2) has become an increasingly pressing issue. Investigating environmental organisms capable of tolerating nTiO2 stress, along with their molecular responses, can help us combat such pollution. In this study, we used multi-omics approaches, genetic manipulation, and physiological and biochemical methods to analyze the responses of Physarum melleum GZ381—which tolerates anatase-type nTiO2 (nTiO2-A) approximately 30 nm in size—and its responsive biomolecules. We observed that the primary molecular response characteristic of GZ381 was related to metabolism. Furthermore, we found that GZ381 utilizes circular RNA08121 in a competitive endogenous RNA network to regulate the transcriptional abundance of many metabolism-related genes, facilitating metabolic reprogramming and conferring obvious anti-nTiO2-A stress capabilities. Based on these findings, we designed mitigation schemes that markedly enhanced the tolerance of various non-tolerant cells to nTiO2-A of different sizes (approximately 30, 60, and 90 nm) under light and dark conditions. Overall, this study reports some important biomolecules that can enhance cellular nTiO2-A resistance and may be used to combat such pollution in the future, deepens the understanding of environmental organisms, especially those tolerant to nTiO2 stress, and provides new inspiration for combating such pollution challenges.